A new species of Dorcadion Dalman, 1817 (Coleoptera: Cerambycidae) from East Kazakhstan - A.E. Abramov (Кавказский энтомологический бюллетень, 2019)
The new species Dorcadion natali sp. n. is described from East Kazakhstan. It is characterized by long lateral thoracic spines, strongly elongate elytra with developed carinae, rather coarse sculpture and relatively long antennomere 3. The new species belongs to the subgenus Acutodorcadion Danilevsky, Kasatkin et Rubenian, 2004 and the most similar to Dorcadion urdzharicum Plavilstshikov, 1937 from which it differs in the following characters (characters of D. urdzharicum in brackets): for both sexes: outer dorsal carinae not reaching basal third of elytra (outer dorsal carinae reaching basal third of elytra); males: elytra on average 2.2 times as long as wide (elytra on average 1.9 times as long as wide); humeral stripe narrow, visibly narrower than interval between humeral and outer dorsal stripes (humeral stripe moderately wide, with the same width as interval between humeral and outer dorsal stripes); outer dorsal stripe very narrow, more than 3 times narrower than interval between dorsal and humeral stripes (outer dorsal stripe moderately narrow, 3 times narrower than interval between dorsal and humeral stripes); humeral carina developed and elevated, with tubercles and wrinkles in basal half, finely serrated in humeral angle area (humeral carina strongly developed, with coarse incisions and weakly tuberculated); antennomere  1 often with dark-red base (antennae completely black); femora and tibiae dark-red, but often completely black (femora and tibiae dark-red, with darkened apices); females: elytra on average 1.7 times as long as wide (elytra on average 1.6 times as long as wide); traces of inner dorsal stripe absent (traces of inner dorsal stripe visible); femora black, tibiae brown (femora and tibiae dark-red, with darkened apices). The third species of the subgenus, Dorcadion songaricum, is smaller (male 14–18 mm, female 16–18.5 mm), has small lateral thoraciс projections and short thoraciс spines, moderately elongate elytra, dark-red antennomer 1 with darkened apex, red or dark-red femora and tibiae. The new species is distributed to the east of Alakol Lake in desert areas on fixed flat sands. Beetles are active in time of flowering ephemeral plants